The sigma factor σ54 (rpoN) functions as a global regulator of antibiotic resistance, motility, metabolism, and virulence in Clostridioides difficile - Yang, Ying; Huang, Tingyu; Yang, Junyi; Shao, Ruirui; Shu, Luhong; Ling, Ping; Lu, Yingjun; Ma, Weihao; Liao, Jian; Guan, Zhizhong; Cui, Guzhen; Qi, Xiaolan; et al. (Frontiers in Microbiology, 2025)
Clostridioides difficile, a major cause of antibiotic-associated diarrhea and pseudomembranous colitis, is increasingly resistant to antibiotics and poses a significant threat due to its regulated virulence. The alternative sigma factor σ54 (rpoN) is known to regulate gene expression broadly, affecting microbial adaptation. Our study investigates how rpoN influences gene expression, physiology, and virulence in C. difficile. We used a modified CRISPR-Cpf1 system to create a rpoN deletion strain (∆rpoN) and a complemented strain (::rpoN) in the CD630 background, comparing their phenotypes and transcriptomes with the wild type. The ∆rpoN strain showed reduced motility and increased susceptibility to seven antibiotics, including β-lactams (amoxicillin, ampicillin, cefoxitin), nitroimidazoles (metronidazole), glycopeptides (vancomycin), fluoroquinolones (norfloxacin), and aminoglycosides (kanamycin). It also exhibited increased toxin gene expression, higher autolysis rates, and enhanced cytotoxicity and virulence in animal models. Additionally, rpoN deletion led to a decrease in glucose metabolic rate, which we attribute to the downregulation of glycolytic enzymes. Transcriptomic analysis indicated that reduced motility in ∆rpoN is due to downregulation of flagellar biosynthesis genes, while increased autolysis is linked to upregulation of autolysin genes like cwp19 and acd. The enhanced release of toxins due to higher autolysis rates contributes to the increased virulence of ∆rpoN. Our findings establish rpoN as a global regulator critical for antibiotic resistance, motility, metabolism, toxin production, and pathogenicity in C. difficile, suggesting its potential as a therapeutic target to mitigate virulence and resistance.